Предмет: Алгебра, автор: xarykolife

Помогите пожалуйста, очень нужно​

Приложения:

Ответы

Автор ответа: daralukanova93
1

Ответ:

2xy(x + y) - 3 {x}^{2} y - x {y}^{2} \\ 2 {x}^{2}y + 2x {y}^{2}    - 3 {x}^{2}y - x  {y}^{2}  \\  {x}^{2}y + x {y}^{2}

Далее подставляем:

( \frac{1}{2} )^{2}  \times  \frac{3}{2}  +  \frac{1}{2}  \times ( \frac{3}{2} )^{2}  =  \frac{1}{4}  \times  \frac{3}{2}  +  \frac{1}{2}  \times  \frac{9}{4}  =  \frac{3}{8}  +  \frac{9}{8}  =  \frac{12}{8}  =  \frac{3}{2}

3/2 или 1.5

Похожие вопросы
Предмет: Физика, автор: орех14